A COMPARISON BETWEEN CHINESE AND INDONESIA IDIOMS IN MEANING AND RHETORIC —TAKING WATER-RELATED IDIOMS AS EXAMPLES - Elly Romy (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2017)
Idiom is not only an important part of Chinese vocabulary, it also reflects the cultural characteristics of a country. Idioms use special rhetoric, unlike sentences used in daily conversation. Sentences in idioms contain artistic values and have different patterns than those used in daily life. Because of their different cultural backgrounds, Indonesian learners have encountered many difficulties in learning Chinese idioms. In order to help the Indonesian learners to eliminate the cultural barriers of learning idioms, the author makes a study of “A Comparison Between Chinese and Indonesia Idioms in Meaning and Rhetoric —Taking Water-related Idioms as Examples”.On the basis of qualitative description and data analysis, this paper draws a conclusion: There are 6 same meanings and 55 different meanings of Chinese and Indonesian idioms with "water". In addition, Chinese idioms with the word "water" use metaphor rhetoric, while Indonesian idioms with "water" use simile besides metaphor  rhetoric.